أثر المشاركة في الأنشطة اللاصفية على الثقة بالنفس لدى طلاب المرحلة الثانوية - حسنين، ريهام أنور عبدالسميع Hassanein, Riham Anwar Abdulsamia; لاشين، ثريا يوسف; عبدالواحد، فاطمة الزهراء عبدالباسط (جامعة حلوان - كلية التربية, 2021)
هدف البحث الحالي إلى كشف وتحديد أثر الأنشطة اللاصفية على الثقة بالنفس، ولتحقيق ذلك استخدمت الباحثة المنهج شبة التجريبي ذو مجموعة تجريبية، وتكونت عينة البحث من (34) طالب وطالبة من الصف الأول الثانوي المشاركين في النشاط المسرحي بمتوسط الحسابي (17.14) وانحراف معياري (0.500)، و(7) طالبات من الصف الأول الثانوي المشاركات في نشاط الاقتصاد المنزلي بمتوسط الحسابي (17.29) وانحراف معياري (0.488)، تتراوح أعمارهم ما بين (17: 18 عام)، وقد تم اختيارهم عن طريق العينة القصدية، وحيث تم استخدام مقياس الثقة بالنفس سيدني روجر (1990) ترجمة عادل عبدالله وتطبيقه علي عينة البحث قبل الاشتراك في الأنشطة اللاصفية في بداية العام الدراسي، ثم عمل قياس للثقة بالنفس (بعدي وتتبعي) في نهاية العام، وتمثلت النتائج في التالي وجود فروق دالة إحصائية في رتب الطلاب المشاركين في نشاط المسرح عند مستوى (4.76) لصالح القياس البعدي، وفي نشاط الاقتصاد المنزلي عند مستوى (2.028) في الثقة النفس لصالح القياس البعدي، مع استمرار تنمية الثقة بالنفس لدى الطلاب في القياس التتبعي. The aim of the current research is to identify the impact of extracurricular activities on self– confidence, and to achieve this, the researcher used the quasi- experimental approach with an experimental group, and the research sample consisted of (34) male and female students from the first secondary grade participating in the atrical activity with an arithmetic mean (17.14) and a standard deviation (0.500), and (7) female first- year secondary school students participating in home economics activity with an arithmetic mean (17.29) and a standard deviation (0.488), their ages ranged between (17: 18 years). Sidney Roger's Self- Confidence Scale (1990) Translated by Adel Abdullah and its application to the research sample before participating in extra- curricular activities at the beginning of the school year, and then a measure of self- confidence (post and follow- up) at the end of the year. The students participating in the theater activity were ranked at a level (0.81) in favor of the post -measurement, and in the home economics activity at a level (0.76) in self- confidence in favor of the post– measurement, with the continued development of the students' self- confidence in the follow- up measurement.
Keywords: الأنشطة التعليمية -- الثقة الذاتية -- المناهج الدراسية -- طلبة المرحلة الثانوية